Rationale, design and methods for a randomised and controlled trial to investigate whether home access to electronic games decreases children's physical activity - Straker, Leon; Abbott, R.; Piek, Jan; Pollock, Clare; Davies, P.; Smith, Anne (BioMed Central, 2009)
Background: Many children are reported to have insufficient physical activity (PA) placing them at greater risk of poor health outcomes. Participating in sedentary activities such as playing electronic games is widely believed to contribute to less PA. However there is no experimental evidence that playing electronic games reduces PA. There is also no evidence regarding the effect of different types of electronic games (traditional sedentary electronic games versus new active input electronic games) on PA. Further, there is a poor understanding about how characteristics of children may moderate the impact of electronic game access on PA and about what leisure activities are displaced when children play electronic games. Given that many children play electronic games, a better understanding of the effect of electronic game use on PA is critical to inform child health policy and intervention.Methods: This randomised and controlled trial will examine whether PA is decreased by access to electronic games and whether any effect is dependent on the type of game input or the child's characteristics. Children aged 10–12 years (N = 72, 36 females) will be recruited and randomised to a balanced ordering of 'no electronic games', 'traditional' electronic games and 'active' electronic games. Each child will participate in each condition for 8 weeks, and be assessed prior to participation and at the end of each condition. The primary outcome is PA, assessed by Actical accelerometers worn for 7 days on the wrist and hip. Energy expenditure will be assessed by the doubly labelled water technique and motor coordination, adiposity, self-confidence, attitudes to technology and PA and leisure activities will also be assessed. A sample of 72 will provide a power of > 0.9 for detecting a 15 mins difference in PA (sd = 30 mins). Discussion: This is the first such trial and will provide critical information to understand whether access to electronic games affects children's PA. Given the vital importance of adequate PA to a healthy start to life and establishing patterns which may track into adulthood, this project can inform interventions which could have a profound impact on the long term health of children.